2007
DOI: 10.1007/s11244-007-0244-5
|View full text |Cite
|
Sign up to set email alerts
|

On the preparation methods for carbon nanofiber-supported Pt catalysts

Abstract: A study of the suitability of different methods for preparing highly loaded, well dispersed carbon nanofiber (CNF) supported Pt catalysts intended for application in fuel cells is reported. Preparation routes that are successfully applied on conventional carbon supports are hampered by the lower surface area and number of surface groups on CNFs. Ion exchange, homogeneous deposition precipitation and impregnation are all techniques that are limited to low metal loading on this CNF support. The most promising me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…49 The diameter of a Pt 100 cluster is ∼2 nm, which is within the cluster size investigated experimentally for fuel cell catalysis applications (i.e., 1-5 nm). 5,7,50 The initial structure of the Pt 100 cluster was found by an energy minimization based on a genetic algorithm (GA). 51 The carbon platelets were built by creating a small graphite slab with a distance of 1.42 Å between carbon atoms within each graphitic layer, which is the distance between first neighbor atoms in graphite.…”
Section: Reactive Force Fieldsmentioning
confidence: 99%
“…49 The diameter of a Pt 100 cluster is ∼2 nm, which is within the cluster size investigated experimentally for fuel cell catalysis applications (i.e., 1-5 nm). 5,7,50 The initial structure of the Pt 100 cluster was found by an energy minimization based on a genetic algorithm (GA). 51 The carbon platelets were built by creating a small graphite slab with a distance of 1.42 Å between carbon atoms within each graphitic layer, which is the distance between first neighbor atoms in graphite.…”
Section: Reactive Force Fieldsmentioning
confidence: 99%
“…In our case, a colloidal Pt solution was dropped onto a carbon coated TEM grid. The colloidal solution is likely to contain Pt of higher valences in the form of PtCl [2][3][4][5][6] or in citrate complexes. Guo et al 13 and Henglein 17 have observed Pt of higher valence state when using the citrate stabilized synthesis methods.…”
Section: Discussionmentioning
confidence: 99%
“…% in order to achieve thin active electrode layers minimizing mass transport limitations and ohmic resistance 2 Tunold, 1933Tunold, -2013 (HDP), impregnation and deposition of colloidal particles. 5,6 The former two methods are limited to low loading catalysts 2 . High loadings are readily achieved by impregnation.…”
Section: Introductionmentioning
confidence: 99%
“…A modified polyol method [25,26] was used for preparation of a 10 wt. % Pt catalyst on platelet carbon nanofibre support.…”
Section: Methodsmentioning
confidence: 99%